Trial/Error. The way to abstraction in Srger - Navarro, Pablo (UXUC - User Experience and Urban Creativity, 2023)
The purpose of the present article is to carry out an evolutionary analysis of Srger’s (Seville, 1983) work in the public space, which has mutated over the years from classical typography within graffiti towards an abstraction that combines its contexts with the artist's own evolution within the studio. All this has given rise to an interesting symbiosis in the form of a dialogue between both work spaces, blurring the between one and the other and enhancing creations that are presented to us as a vestige of an intense creative process.